Aplikasi Seluler untuk Pencegahan Insiden Keselamatan Pasien Anak - Endang Puspita Sari; Sigit Mulyono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the role of mobile applications in preventing safety incidents for pediatric patients in hospitals. The method used was a literature search through searching the online databases Science Direct, ProQuest, Scopus, and Google Scholar published in 2018-2022 with the keywords mobile application, patient safety, child, hospitalized, and patient education. The research results showed that children's safety awareness levels increased after being given a safety incident prevention program using a mobile application. In conclusion, mobile applications for preventing pediatric patient safety incidents in hospitals are practical, feasible, and acceptable to children, families, and nurses. Keywords: Children, Mobile Applications, Patient Safety, Safety Incident Prevention, Pediatric Nurses